2020
DOI: 10.1111/anec.12791
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of initial QRS analysis in anterior STEMI: Correlation with left ventricular systolic dysfunction, serum biomarkers, and cardiac outcomes

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
(35 reference statements)
1
2
0
Order By: Relevance
“…Thus, in our study, a pathological Q wave was more often registered in patients with lEF (almost twice more often than in patients with mEF), which is consistent with some other studies that also demonstrated the association of this ECG sign with reduced EF below 40% [ 45 , 46 ]. The presence of a pathological Q wave in ECG often points to existing myocardial fibrosis.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, in our study, a pathological Q wave was more often registered in patients with lEF (almost twice more often than in patients with mEF), which is consistent with some other studies that also demonstrated the association of this ECG sign with reduced EF below 40% [ 45 , 46 ]. The presence of a pathological Q wave in ECG often points to existing myocardial fibrosis.…”
Section: Discussionsupporting
confidence: 92%
“…The presence of pathological Q-waves on the admission ECG is predictive of increased mortality, heart failure and cardiogenic shock after STEMI [3,4,72]. According to Lopez-Castillo et al, the sum of Q-wave depth at discharge performs better than the number of leads with pathological Q-waves as an independent predictor of LVSD development [73].…”
Section: Pathological Q-wavesmentioning
confidence: 99%
“…The QRS complex morphology, and ST-segment changes, have already been described as potential predictors of certain outcomes. Some of the previous work analyzed the role of poor R wave progression, with a dominant QS pattern in V3, in reduced left ventricular ejection fraction (LVEF) prediction, as well as the influence of QRS complex width on left ventricular systolic dysfunction (LVSD) development, increased risk of heart failure (HF), and death [11,12]. Some of the more recent important ECG parameters are fragmented QRS (fQRS) and QRS distortion, which showed themselves useful in determining reperfusion success, and stratifying high cardiac risk patients [8].…”
Section: Introductionmentioning
confidence: 99%